Comparison of four softening agents used on formalin-fixed paraffin-embedded nail biopsies with inflammatory disease. (2nd January 2020) - Sharma, Pooja; Sharma, Sonal; Kaul Murthy, Subuhi; Singal, Archana; Grover, Chander
ABSTRACT: Obtaining high-quality sections of the nail plate poses a significant challenge to histopathology technicians world over. Nail is a heavily keratotic hard tissue that tends to split or tear while sectioning when processed and embedded in a routine manner. Many agents such as phenol, alcohol, and thioglycolate have been tried for the purpose of softening a variety of experimental materials. However, there is no clear consensus on any single agent. The study was conducted with the aim of evaluating and comparing the role of various compounds as softening agents for nail biopsies with inflammatory disease. Thirty paraffin-embedded nail biopsies were subjected to four softening agents: distilled water (DIH2 0), 30% potassium hydroxide (KOH), hair removal cream, and fabric conditioner. The ease of sectioning, the incidence of juddering (i.e. 'venetian blind' effect), and the shattering of tissue were recorded. Hematoxylin and eosin-stained sections were examined microscopically. Sectioning was very easy after using fabric conditioner, with good quality sections, and hair removal cream produced comparable results. The incidence of juddered, shattered sections after using hair removal cream was considerably higher (63.33%) compared to fabric conditioner-treated nails (16.67%). Microtomy of nail biopsies was found to be easiest after using 30% KOH with moderate section quality. DIH2 O could neither allow easier sectioning nor obtain good sections for interpretation. Fabric conditioner and hair removal cream proved to be the effective keratin softeners, while 30% KOH worked effectively when the nail plate alone was submitted for histological examination.